Strategi Sukses Penulisan Konten untuk Meningkatkan Brand Awareness dan Penjualan - Monica Nelly Agustine; Fajar Rizki Anandasari; Anindita Nadine K; Sinta Farida; Budi Erisaputri; Risqi Ihsal Wibisono; Gunawan Witjaksono (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2024)
As times progress in the fast-paced and dynamic digital era, the ability to present creativity and information in an interesting and high-quality manner has become very important, especially for the brands being promoted. Writing content planning is one of the main forms of brand or product development planning through content writing so that the final goal can be achieved. Likewise, students at SMK N 1 Semarang need creativity in producing written content, especially students majoring in broadcasting to attract the attention of audiences in the digital marketing field. Service entitled "Successful Content Writing Strategy to Increase Brand Awareness and Sales", with a service team by Monica Nelly Agustine, Fajar Rizki Anandasari, Anindita Nadine k, Sinta Farida, Budi Erisaputri, Rizqi Ihsal Wibisono. SMK N 1 Semarang students are given education and creativity training about writing correct content planning and being able to attract the attention of the audience so that they have knowledge and experience in this field.